2018
DOI: 10.1038/s41598-018-19836-7
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Derived Short Chain Fatty Acids Induce Circadian Clock Entrainment in Mouse Peripheral Tissue

Abstract: Microbiota-derived short-chain fatty acids (SCFAs) and organic acids produced by the fermentation of non-digestible fibre can communicate from the microbiome to host tissues and modulate homeostasis in mammals. The microbiome has circadian rhythmicity and helps the host circadian clock function. We investigated the effect of SCFA or fibre-containing diets on circadian clock phase adjustment in mouse peripheral tissues (liver, kidney, and submandibular gland). Initially, caecal SCFA concentrations, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
184
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(202 citation statements)
references
References 45 publications
4
184
0
1
Order By: Relevance
“…; Pluznick, ; Tahara et al . ). Gut microbial‐derived SCFAs are also increasingly implicated in emotional processing and behaviour, as butyrate has been shown to ameliorate cognitive impairments in a model of vascular dementia and in mid‐adult high‐fat‐diet‐induced obese mice (Liu et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Pluznick, ; Tahara et al . ). Gut microbial‐derived SCFAs are also increasingly implicated in emotional processing and behaviour, as butyrate has been shown to ameliorate cognitive impairments in a model of vascular dementia and in mid‐adult high‐fat‐diet‐induced obese mice (Liu et al .…”
Section: Introductionmentioning
confidence: 97%
“…It is therefore essential to emphasise that physiologically relevant levels of acetate and propionate have been reported to directly influence the brain (Perry et al 2016;Hoyles et al 2018). Considering the plethora of ways in which they can affect the host, it's not surprising that SCFAs have been implicated in numerous physiological functions such as gastrointestinal functionality, host metabolism, blood-pressure regulation, circadian rhythm and (neuro)immune function (Koh et al 2016;Erny et al 2017;Pluznick, 2017;Tahara et al 2018). Gut microbial-derived SCFAs are also increasingly implicated in emotional processing and behaviour, as butyrate has been shown to ameliorate cognitive impairments in a model of vascular dementia and in mid-adult high-fat-diet-induced obese mice Arnoldussen et al 2017), and propionate is able to reduce anticipatory reward responses to high-energy foods in the human striatum (Byrne et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting model using the cyclical parthenogenetic insect Daphnia pulex showed that temperature altered energy allocation, as expected, but did not systematically match with the consequences of calorie restriction in terms of longevity (Schwartz et al ., ). Factors such as the circadian rhythm and quality of light are seldom taken into account, despite the fact that they have a considerable impact on the host (Cribbet et al ., ) as well as on microbial life cycles (Borriss et al ., ; Tahara et al ., ). The consequence is that the food intake time points have substantial consequences that are rarely considered seriously (Hutchison et al ., ).…”
Section: Genomes and Evolution: The Gut Microbiota Of Man And Great Apesmentioning
confidence: 97%
“…The precise mechanisms of how microbiota can exert this role need further investigation. Microbiota‐derived metabolites such as short‐chain fatty acid, bile acids, lipopolysaccharides, and B vitamins have been implicated in mediating the information from the gut microbiota to the host . Most of these studies focused on the influence of microbiota on the host's circadian clock machinery.…”
Section: The Effects Of Microbiota On Host's Rhythmic Physiologymentioning
confidence: 99%